Shockwave - Black, Peter Jay (Black, Peter Jay. Urban Outlaws., 2016)
Deep beneath London, five extraordinary youths, orphans who bonded over their shared sense of justice, have formed the Urban Outlaws and dedicated themselves to outsmarting criminals and performing Random Acts of Kindness (R.A.K.s), but now they are in serious trouble when they face the ultimate weapon - Medusa. Hector Del Sarto used them to spread the deadly Medusa virus and now the whole of London is in lockdown. Only Hector and his father have the antidote. Can Jack, Charlie, Obi, Slink and Wren work together to bring down the Del Sartos once and for all? The whole city depends on them! The Urban Outlaws face their toughest challenge yet in the final book of this high-octane adventure series for fans of Robert Muchamore, Anthony Horowitz and Alex Scarrow.